2013
DOI: 10.1007/s00213-013-3209-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amphetamine and methylphenidate on delay discounting in rats: interactions with order of delay presentation

Abstract: Rationale Drug effects on delay discounting are thought to reflect changes in sensitivity to reinforcer delay, although other behavioral mechanisms might be involved. One strategy for revealing the influence of different behavioral mechanisms is to alter features of the procedures in which they are studied. Objective This experiment examined whether the order of delay presentation under within-session delay discounting procedures impacts drug effects on discounting. Methods Rats responded under a discrete-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 37 publications
9
77
1
Order By: Relevance
“…The behavioral procedure used in the current study was based on the procedure developed by Evenden and Ryan (1996) and recently described by Tanno et al (2014). Daily sessions were divided into 5 blocks, each of which comprised 2 forced trials followed by 5 choice trials.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The behavioral procedure used in the current study was based on the procedure developed by Evenden and Ryan (1996) and recently described by Tanno et al (2014). Daily sessions were divided into 5 blocks, each of which comprised 2 forced trials followed by 5 choice trials.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the effects of stimulant drugs such as amphetamine on delay discounting can differ qualitatively, either increasing or decreasing discounting, depending upon whether the delay period is paired with a unique stimulus (e.g., Cardinal et al 2000). A recent study (Tanno et al 2014) showed that the effects of amphetamine and methylphenidate on performance under a delay discounting procedure vary depending on the order in which delays are presented within the session. Both drugs increased choice of the larger delayed reinforcer in rats responding under an ascending order of delay, consistent with effects reported by others (e.g., Barbelivien et al 2008; Cardinal et al 2000; Huskinson et al 2012; Pitts and McKinney 2005; Slezak and Anderson 2011; Slezak et al 2013; Van Gaalen et al 2006; Winstanley et al 2003; 2005), but markedly decreased choice of the larger reinforcer in a separate group of rats responding under a descending order.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that procedural variables such as order of delay presentation (ascending vs. descending delay; St. Onge et al 2010;Tanno et al 2014) and signaled vs. unsignaled trials (e.g. Cardinal et al 2000) can influence experimental outcomes.…”
Section: -Ht 2c Receptors and The Regulation Of Impulsive Behaviourmentioning
confidence: 98%